From Edmonton to Lantidra and beyond: immunoengineering islet transplantation to cure type 1 diabetes - Mbaye, El Hadji Arona; Scott, Evan A.; Burke, Jacqueline A. (Frontiers in Transplantation, 2025)
Type 1 diabetes (T1D) is characterized by the autoimmune destruction of insulin-producing β cells within pancreatic islets, the specialized endocrine cell clusters of the pancreas. Islet transplantation has emerged as a β cell replacement therapy, involving the infusion of cadaveric islets into a patient's liver through the portal vein. This procedure offers individuals with T1D the potential to restore glucose control, reducing or even eliminating the need for exogenous insulin therapy. However, it does not address the underlying autoimmune condition responsible for T1D. The need for systemic immunosuppression remains the primary barrier to making islet transplantation a more widespread therapy for patients with T1D. Here, we review recent progress in addressing the key limitations of islet transplantation as a viable treatment for T1D. Concerns over systemic immunosuppression arise from its potential to cause severe side effects, including opportunistic infections, malignancies, and toxicity to transplanted islets. Recognizing the risks, the Edmonton protocol (2000) marked a shift away from glucocorticoids to prevent β cell damage specifically. This transition led to the development of combination immunosuppressive therapies and the emergence of less toxic immunosuppressive and anti-inflammatory drugs. More recent advances in islet transplantation derive from islet encapsulation devices, biomaterial platforms releasing immunomodulatory compounds or surface-modified with immune regulating ligands, islet engineering and co-transplantation with accessory cells. While most of the highlighted studies in this review remain at the preclinical stage using mouse and non-human primate models, they hold significant potential for clinical translation if a transdisciplinary research approach is prioritized.